Pengaruh Variasi Produk, Digital Marketing dan Citra Merek terhadap Keputusan Pembelian Kopi Janji Jiwa di Batam - Suswati, Liza; Nainggolan, Nora Pitri (Jurnal Disrupsi Bisnis, 2024)
This research aims to evaluate the influence of product variations, digital marketing and brand image on purchasing decisions for Janji Jiwa coffee in Batam. This research population focuses on a group of consumers in Batam who have purchased Janji Jiwa coffee products although their number cannot be ascertained with certainty. Sampling was carried out using the Lameshow formula and 100 respondents were selected using purposive sampling techniques. The data analysis process involves the use of multiple linear regression methods which include data quality testing, classical assumption testing, influence testing and hypothesis testing. The results of multiple linear regression analysis show that product variations have an influence of 22.7% on purchasing decisions. Digital marketing has an influence of 18.3% on purchasing decisions. Brand image has an influence of 33.4% on purchasing decisions. Analysis of the coefficient of determination (R2) shows that together, product variety, digital marketing and brand image contribute 36.2% to the observed variation in purchasing decisions. Furthermore, the results of the t test and F test confirm that there is a positive and significant influence, both partially and overall, between product variations, digital marketing and brand image on the decision to purchase Janji Jiwa coffee in Batam.